Adaptation of BPSK/TH/UWB Parameters Using RAKE Receiver with IPI in WPAN Indoor Multipath Fading Channels - Natiq A. Ali; Saleh M. Al-Qaraawy (Engineering and Technology Journal, 2008)
In this paper, the performance of a PRAKE receiver for a pulse based ultra-wideband(UWB) communications system is studied in a realistic channel model that is based on anextensive set of indoor channel measurements. The adaptation of parameters of Binary Phaseshift Keying/Time Hopping/Ultra Wideband (BPSK/TH/UWB) using PRAKE receiver isshown to contribute to a mitigation of the Inter-pulse interference (IPI). This work is basedon the adaptation of multiple access parameters to mitigate the effect of IPI in a certain level.This study is done on the Wireless Personal Area Network (WPAN) IEEE802.15.3a, CM3channel which is used for indoor network applications. Simulated results show theperformance improvement in terms of BER. The results show improvements in the BER dueto the adaptation of the values of number of pulses Ns and the number of chips per frame Nh.This is done simply by adjusting the bit rate Rb to a certain value and varies the value of Nsand Nh such that their product has a similar value. In this way the IPI is reduced because it ishardly depends on Ns and Nh